Tax Reform Through the Reconstruction of Disputes and Law Enforcement Based on the Pancasila Legal Philosophy - Radhyca Nanda Pratama; Khaidar Alifika El Ula; Bazarova Dildora Baxadirovna (NOVUM : JURNAL HUKUM, 2024)
Problems with tax disputes in Indonesia include the burden of cases in the Tax Court that have not been decided and as well as the resolution of tax disputes in two courts, namely the PTUN and the Tax Court. This gives rise to inefficiencies in resolving tax disputes. This research aims to formulate tax reform by reconstructing disputes and enforcing tax law based on the values of Pancasila as the ideals of Indonesian law. This research is normative legal research by prioritizing, prioritizing conceptual, statutory, and comparative approaches. The results of the research show that the urgency of resolving disputes and enforcing tax law which refers to the values of Pancasila as the ideals of Indonesian law is expected to be able to apply the three values in Pancasila, namely deliberation-consensus, the value of efficiency and the value of justice which are expected to be applied used in disputes and enforcement of tax law which is more efficient. Reconstructing disputes and enforcing tax law, which is based on the three main central values in Pancasila, namely the value of deliberation and consensus, the value of efficiency, and the value of justice, requires tax reform through the revision of statutory regulations using the omnibus law method. This requires involves the formulation of the Tax Dispute Law using the omnibus law method, which revises several related laws such as the Tax Court Law, the HPP Law, and various other related associated laws and regulations. In practice, the idea of dispute reconstruction and tax law enforcement needs to be carried out by prioritizing tax mediation, resolving tax disputes in the Tax Court, and optimizing preventive approaches such as e-tax consultation.